Suriname : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues Paper carries out an empirical analysis of the effects of policies and external shocks on economic activity in Suriname. The estimates are broadly consistent with prior empirical findings. The results reveal a strong contemporaneous correlation between credit and demand, while the empirical link between exports and demand seems slightly weaker. The results for import demand point to a strong correlation between imports and exports. The export variable is highly significant and explains a large fraction of the total variation in imports. An increase in exports of 1 percent is associated with a 0.61 percent increase in imports.